Carbon Dioxide Recycling into Fuels and Valuable Chemicals - Venko Beschkov (Energies)
The present review proposes an approach for remediation of atmosphere pollution by carbon dioxide. The global economic growth nowadays requires extensive energy consumption. Energy is produced traditionally by combustion of carbon containing fuels, resulting in the release of large amounts of carbon dioxide in the atmosphere. These emissions of released CO2 lead to the greenhouse effect on the atmosphere with subsequent impact on the global climate. Remediation of this harmful effect requires reduction in CO2 emissions. In addition to improving the efficiency of energy consumption, this reduction can be also accomplished by the recycling of carbon dioxide into fuels and useful commodities. This conversion of CO2 into fuels and commercial products leads to multiple benefits such as reduction in carbon emissions and greenhouse gases, production of value-added goods, thus reducing oil consumption and associated pollutions of the environment. This review summarizes the efforts to remove, or at least to remediate, the release of carbon dioxide in the atmosphere by its conversion to value-added products prior to discharging. Some of these products are urea, methanol, formic acid, some polymers of practical importance, light hydrocarbons and methane. The recent achievements in chemical catalysis, electrochemistry, bioelectrochemistry and photocatalysis are considered. Discussion on the feasibility of the considered methods compared to the traditional technologies is made. It is concluded that although production of value-added chemicals by carbon dioxide recycling is not yet competitive, it seems promising in the future when its economic feasibility will become a reality.